Valorization of quality of oil extracted from grape seeds with application in cosmetics production - Eugenia MELENTIEV; Lidia CALMUȚCHI; Doina PITUȘCAN (Acta et Commentationes Exact and Natural Sciences, 2020)
The oil extracted from the grape seeds can be a by-product for wine, rich in nutrients, polyphenol compounds, fatty acids, vitamins, minerals, which have an essential role in the cosmetics, alimentation and pharmaceutical industries. The article describes the composition of the oil extracted the grape seeds, Isabella variety, and the evaluation of its valuable compounds with seeds, Isabella variety, and the evaluation of its valuable with antioxidant properties.